BIBLIOMETRIC STUDY ON THE IMPORTANCE OF USING CREATIVE ACCOUNTING IN FINANCIAL REPORTING - Alina MARCUTA; Delia RADOI; Alina Cristina NUTA; Florian Marcel NUTA; Liviu MARCUTA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The current research aimed to analyze scientific production, using bibliometric analysis as a research method, with the aim of understanding the current structure of studies and future research directions related to creative accounting, how to use creative accounting practices and the role or in financial reporting. 13,463 documents published between 1999-2023 were identified in the Web of Science database and 24,461 researches in the Scopus database, which were refined according to 2 more terms: "user perception" and "impact on financial results" . 80 articles were retained for the last stage of research, whose scientific content was analyzed with the help of VOSviewer software, performing both descriptive analysis and performance analysis, as well as scientific mapping from the perspective of the conceptual, intellectual and social structure. In order to determine research gaps, the 10 most relevant and influential papers were analyzed, these being established in relation to the number of citations, which was between 32 and 168. The research results highlighted the fact that half of the analyzed articles are reviews of specialized literature, which highlights gaps in primary research on creative accounting. What is worth noting is the fact that case studies or empirical studies based on questionnaires or the analysis of data sets related to financial reporting, address both aspects related to large companies listed on the stock exchange, as well as those related to medium and small companies. The studies followed the techniques of creative accounting and the way of financial reporting, both for private and state companies, both companies that benefited from external and internal financing, demonstrating the complex interest in the issue of using creative accounting. The gaps identified in this study will constitute future research directions in the field.